MEDIA ENGLISH EDUCATIONAL GAME (EEG) BERBASIS ANDROID PADA MATERI KIND OF TEXT - Putra, Ino Angga; Harianto, Harianto; Airlangga, Primadi (JoEMS (Journal of Education and Management Studies), 2021)
This study aims to develop English learning media for class XI students in high school, especially in the Kind of Text material that suits their needs. In addition, the main goal of the researcher is to design an Android-based educational game media for English subjects in reading skills on Kind of Text material in high school to help students make it easier to learn English and to find out how appropriate the educational game media is. The researcher uses the Research and Development method which is adapted from the development of ADDIE. English learning media is named English Education Game (EEG). This English learning media is an application designed to help students increase their interest in learning English in the ability to read a text. This English learning media was validated by media experts and material experts before being tested on students. While the research instrument is an interview with one of the English teachers at MA Mambaul.Ulum Megaluh Jombang. The results of this study indicate that 1) the results of the media expert score are 4.60. 2) the results of the material expert score 4.3. 3) the result of the field test score is 4.43. Based on the results above, the researcher concludes that the English Education Game (EEG) media is suitable for use in learning English.